2021
DOI: 10.1001/jamaophthalmol.2020.4741
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Drug Use–Related Endogenous Endophthalmitis Hospitalizations in the United States, 2003 to 2016

Abstract: IMPORTANCEComplications arising from the nationwide opioid epidemic led to an increase in health care use. Few studies have investigated whether this is reflected in hospital admissions for endogenous endophthalmitis. OBJECTIVE To report changing trends in epidemiology, risk factors, hospital course, and costs associated with drug use-related endogenous endophthalmitis hospitalizations in the United States from 2003 to 2016. DESIGN, SETTING, AND PARTICIPANTS Nationwide, retrospective cross-sectional study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…As reported in the literature [ 17 , 18 , 19 , 20 ], patients with a history of IVDU exhibit a higher risk of EFE because of the direct inoculation of pathogens into the bloodstream. Mir et al [ 21 ] reviewed 56,839 cases of endogenous endophthalmitis hospitalizations in the United States and reported that 13.7% had a history of IVDU. In a previous study, 9.8% and 1.8% of patients with IVDU had a diagnosis of Candida infection and disseminated candidiasis, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in the literature [ 17 , 18 , 19 , 20 ], patients with a history of IVDU exhibit a higher risk of EFE because of the direct inoculation of pathogens into the bloodstream. Mir et al [ 21 ] reviewed 56,839 cases of endogenous endophthalmitis hospitalizations in the United States and reported that 13.7% had a history of IVDU. In a previous study, 9.8% and 1.8% of patients with IVDU had a diagnosis of Candida infection and disseminated candidiasis, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mir et al [ 21 ] reviewed 56,839 cases of endogenous endophthalmitis hospitalizations in the United States and reported that 13.7% had a history of IVDU. In a previous study, 9.8% and 1.8% of patients with IVDU had a diagnosis of Candida infection and disseminated candidiasis, respectively [ 21 ]. However, no statistical difference in Aspergillus infection was observed between patients with IVDU and patients without IVDU.…”
Section: Discussionmentioning
confidence: 99%
“…An important contributing cause of endogenous endophthalmitis is intravenous drug use: Mir et al reviewed 56,839 cases of endogenous endophthalmitis hospitalizations in the United States and found that 13.7% had a history of drug dependence or use. If these, 9.8% had Candida infection and 1.8% had disseminated candidiasis [53]. Furthermore, the incidence of endogenous endophthalmitis associated with drug dependence or use has increased from 0.08 per 100,000 people in 2003 to 0.32 per 100,000 people in 2016 [53].…”
Section: Endogenous Endophthalmitismentioning
confidence: 99%
“…To date, there has been no investigation into the pattern of opioid prescribing by optometrists. Previous studies examining the opioid prescribing rates of eye care providers have focused on the amount of general opioid prescriptions written by ophthalmologists 8–15 . The role of the optometrist prescribing opioids is relevant not only for analysis of clinical practice patterns for primary eye care, but with the trend of co-managed surgical patients, optometrists are often co-managing post-operative surgical patients 24 to 36 hours after surgery 16 .…”
mentioning
confidence: 99%
“…Previous studies examining the opioid prescribing rates of eye care providers have focused on the amount of general opioid prescriptions written by ophthalmologists. [8][9][10][11][12][13][14][15] The role of the optometrist prescribing opioids is relevant not only for analysis of clinical practice patterns for primary eye care, but with the trend of co-managed surgical patients, optometrists are often co-managing post-operative surgical patients 24 to 36 hours after surgery. 16 The purpose of this study is to examine the prescription rates and prescribing trends of opioids by optometrists listed in the Centers for Medicare & Medicaid Services (CMS) part D database.…”
mentioning
confidence: 99%